SESAJEN IN THE PERSPECTIVE OF IBN KATHIR: INTERPRETATION OF SURAH AN-NISA, VERSE 48 - Achsanudtaqwin, Achris (Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2023)
Sesajen has been a controversial topic from ancient times to the present. This ritual involves offering food and other objects in religious or customary ceremonies to communicate with supernatural powers. The tradition of sesajen in Islam reflects a cultural heritage with spiritual and religious practices, and an understanding of this tradition is essential to understanding the Islamic view of sesajen. This study explores Ibn Kathir's interpretation of the tradition of sesajen in the context of Surah An-Nisa verse 48, to understand his views and arguments regarding sesajen in Islam. This study uses a literature review to explore Ibn Kathir's perspective on sesajen through his interpretation of the Qur'an. This involves analyzing literature, including Ibn Kathir's works, to detail his arguments and views on the tradition of sesajen. Ibn Kathir's interpretation emphasizes the importance of maintaining the sanctity of worship and warns against deviation from the principle of monotheism, providing valuable guidance for Muslims today. His interpretation contributes to strengthening the religious identity, and countering negative cultural influences while addressing modern challenges.